2016
DOI: 10.1515/epoly-2016-0047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon sources on physicochemical properties of bacterial cellulose produced from Gluconacetobacter xylinus MTCC 7795

Abstract: In this study, the effect of modified Hestrin Schramm (HS) medium supplemented with different carbon sources viz., glucose, fructose, galactose and lactic acid on the yield and physicochemical properties of bacterial cellulose (BC) produced from Gluconacetobacter xylinus strain MTCC 7795 in shake flask culture conditions was investigated. Growth studies indicated that all carbon sources supported the growth of bacteria, though specific growth rate and doubling time differs. Fructose gave the highest cellulose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The production of BC using yeast extract was approximately 2 folds higher than peptone or tryptone in the production medium. The reason might be that yeast extract has a rich source of nutrients including carbon, amino acids and vitamin B complex essential for for stimulating the cellular growth as well as the synthesis of product 67 , 68 . Similar to the findings, Embuscado et al, 1994 reported that inorganic N-sources such as sodium nitrate as well as ammonium sulphate resulted in relatively low production of BC during fermentation 69 .…”
Section: Resultsmentioning
confidence: 99%
“…The production of BC using yeast extract was approximately 2 folds higher than peptone or tryptone in the production medium. The reason might be that yeast extract has a rich source of nutrients including carbon, amino acids and vitamin B complex essential for for stimulating the cellular growth as well as the synthesis of product 67 , 68 . Similar to the findings, Embuscado et al, 1994 reported that inorganic N-sources such as sodium nitrate as well as ammonium sulphate resulted in relatively low production of BC during fermentation 69 .…”
Section: Resultsmentioning
confidence: 99%
“…The biofilm is then dried using various methods (most commonly ambient air-drying) until a constant weight is achieved, from which the overall yield of BC (in terms of weight rather than purity) is calculated. 23,25,[27][28][29] Studies examining the performance of BC as a textile in apparel have focused on the production of BC sheets, 30,31 the ability of the sheet to be formed into garment shapes 32 or the response of the sheet to textile coloration and finishing techniques from an aesthetic viewpoint. 33,34 Whilst previous studies have postulated the use of BC as an apparel textile, with some suggesting it could be seen as a replacement to animal leather, 7,35 to the authors' knowledge, no studies to date have specifically tested the sheets as an apparel textile to establish their performance characteristics and suitability for fashion garment end-use.…”
mentioning
confidence: 99%
“…24,25 Schramm and Hestrin 26 developed the ‘standard’ (but undefined) complex growth medium (commonly known as H&S) consisting of glucose, bactopeptone and yeast extract. 23,25,27,28 This medium is commonly used in experiments that remove the developed pellicle/biofilm from the surface of the liquid medium, rinsing using distilled water and NaOH to lyse any residual bacterial cells. The biofilm is then dried using various methods (most commonly ambient air-drying) until a constant weight is achieved, from which the overall yield of BC (in terms of weight rather than purity) is calculated.…”
mentioning
confidence: 99%
See 1 more Smart Citation